Brand Image Vs Brand Love: Which One Matters More For Customer Loyalty Among Mobile Legends Users? - Aziezy, Enrico; Purnomo, Sodik Dwi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study examines the impact of brand image (X1) and brand love (X2) on customer loyalty (Y), with customer engagement (Z) serving as a mediating variable among Mobile Legends: Bang-Bang users in Purwokerto. The research seeks to elucidate how these constructs interact and contribute to customer retention within the competitive mobile gaming sector. A total of 120 respondents were selected using a non-probability sampling approach, specifically employing accidental sampling. Data were analyzed through the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method using the SmartPLS 4.0 software package. The findings reveal that customer engagement significantly mediates the positive relationship between brand love and customer loyalty, indicating that an emotional attachment to the brand enhances loyalty through active customer involvement across various markets. Conversely, customer engagement does not mediate the relationship between brand image and customer loyalty, and brand image was found to exert no direct effect on loyalty. These outcomes underscore the critical importance of brand love in fostering customer loyalty, suggesting that strategies aimed solely at enhancing brand image may not be sufficient to drive sustained customer retention.